LINGUISTIC FEATURES OF YOUTH JARGON - Ostapenko, Svitlana; Hanna, Udovichenko (SWorld-Ger Conference proceedings, 2025)
The paper deals with the issue of linguistic characteristics of youth jargon. The authors analyse lexical, morphological, phonetic and syntactic features of jargon. The key lexical features include borrowings, abbreviations, neologisms, reinterpretations